Effects of Opioids Given to Facilitate Mechanical Ventilation on Sleep Apnea After Extubation in the Intensive Care Unit. Issue 1 (20th November 2017) - Timm, Fanny P; Zaremba, Sebastian; Grabitz, Stephanie D; Farhan, Hassan N; Zaremba, Stefanie; Siliski, Elizabeth; Shin, Christina H; Muse, Sandra; Friedrich, Sabine; Mojica, James E; Kurth, Tobias; Ramachandran, Satya-Krishna; et al.
Abstract: Study Objectives: Following extubation in the intensive care unit (ICU), upper airway (UA) edema and respiratory depressants may promote UA dysfunction. We tested the hypothesis that opioids increase the risk of sleep apnea early after extubation. Methods: Fifty-six ICU patients underwent polysomnography the night after extubation. Airflow limitation during wakefulness was identified using bedside spirometry. Correlation and ordinal regression analyses were used to quantify the effects of preextubation opioid dose on postextubation apnea–hypopnea index (AHI) and severity of sleep apnea and whether or not inspiratory airway obstruction (ratio of maximum expiratory and inspiratory airflows at 50% of vital capacity [MEF50/MIF50] ≥ 1) during wakefulness predicts airway obstruction during sleep. Data were adjusted for age, gender, body mass index, as well as a generalized propensity score balanced for APACHE II, score for preoperative prediction of obstructive sleep apnea, duration of mechanical ventilation, chronic obstructive pulmonary disease, and a procedural severity score for morbidity. Results: Sleep apnea (AHI ≥ 5) was present in 40 (71%) of the 56 patients. Morphine equivalent dose given 24 hours prior extubation predicted obstructive respiratory events during sleep ( r = 0.35, p = .01) and sleep apnea (odds ratio [OR] 1.17; 95% confidence interval [CI] 1.02–1.34). Signs of inspiratory UA obstruction (MEF50/MIF50 ≥ 1) assessed by bedside spirometry were strongly associated with sleep apnea (OR 5.93; 95% CI 1.16–30.33). Conclusions: High opioid dose given 24 hours prior to extubation increases the likelihood of postextubation sleep apnea in the ICU, particularly in patients with anatomical vulnerability following extubation.